2008
DOI: 10.1038/nphys1073
|View full text |Cite
|
Sign up to set email alerts
|

Quantum states and phases in driven open quantum systems with cold atoms

Abstract: An open quantum system, whose time evolution is governed by a master equation, can be driven into a given pure quantum state by an appropriate design of the system-reservoir coupling. This points out a route towards preparing many body states and non-equilibrium quantum phases by quantum reservoir engineering. Here we discuss in detail the example of a driven dissipative Bose Einstein Condensate of bosons and of paired fermions, where atoms in an optical lattice are coupled to a bath of Bogoliubov excitations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
1,255
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,132 publications
(1,292 citation statements)
references
References 32 publications
14
1,255
0
3
Order By: Relevance
“…This could be achieved by modifying the properties of the reservoir to form a bound state and to approach the non-Markovian regime via the potential usage of reservoir engineering [21][22][23]. Many experimental platforms (e.g., mesoscopic ion traps [21], cold atom BECs [22], and the photonic crystal materials [14] have exhibited the controllability of decoherence behavior of relevant quantum systems through optimally designing the size (i.e., modifying the spectrum) of the reservoir and/or the coupling strength between the system and the reservoir. It is also worth mentioning that a proposal aimed at simulating the spin-Boson model, which is relevant to the one considered in this paper, has been reported in a trapped ion system [24].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This could be achieved by modifying the properties of the reservoir to form a bound state and to approach the non-Markovian regime via the potential usage of reservoir engineering [21][22][23]. Many experimental platforms (e.g., mesoscopic ion traps [21], cold atom BECs [22], and the photonic crystal materials [14] have exhibited the controllability of decoherence behavior of relevant quantum systems through optimally designing the size (i.e., modifying the spectrum) of the reservoir and/or the coupling strength between the system and the reservoir. It is also worth mentioning that a proposal aimed at simulating the spin-Boson model, which is relevant to the one considered in this paper, has been reported in a trapped ion system [24].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The quantum state engineering based on the dynamics in the open quantum systems [13], in particular in the optical lattices [14], is a well-known idea. As distinct from the previous proposal of the quantum state engineering in the optical lattices (see also the recent study [15]), where the inter-site atomic currents are coupled to reservoirs, in our case the dissipation acts locally and incoherently on a periodic sublattice of the lattice sites, whereas the condensate is driven to a non-local coherent state.…”
Section: Introductionmentioning
confidence: 99%
“…For the interaction-dominated regime this increase is logarithmic, whereas it is a power law in the tunneling-dominated regime. Nonetheless, for any non-vanishing cavity decay rate, the correlation length always remains finite.Related questions are of high relevance for ultra-cold atoms [24], ions [25] , superconducting circuits [26] or exciton-polariton condensates [7]. For the latter, functional renormalization group approaches showed that, arXiv:1401.5776v2 [quant-ph]…”
mentioning
confidence: 99%
“…Related questions are of high relevance for ultra-cold atoms [24], ions [25] , superconducting circuits [26] or exciton-polariton condensates [7]. For the latter, functional renormalization group approaches showed that, arXiv:1401.5776v2 [quant-ph]…”
mentioning
confidence: 99%